3-Dimensional mapping of underwater surface for navigation using underwater ultrasonic piezoelectric transducer - Hossain, Navan Tanjeem; Khan, Rahat Mahmood; Rahman, Saifur (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.